The question really does depend on getting the explicit formula.
Explicit
t1 = 25
t2 = 23 The difference is 2 to get to 25
t3 = 19 which means that you need 6 to get back to 25
t3 = 25 - 2*3
t3 = 25 - 2*(2^(n-1) - 1)
t3 = 25 - 2*(2^(2) - 1 )
t4 = 11 which means that you need 14 to get back to 25
t4 = 25 - 2*7
t4 = 25 - 2*(2^3 - 1)
t5 = 25 - 2*(2^4 - 1)
t5 = 25 - 2*(16 - 1)
t5 = 25 - 2*15
t5 = - 5
tn = 25 - 2*(2^(n- 1) - 1) Explicit Answer
====================
Recursive
t1 = 25
t2 = 23 which is t1 - 2^(n-1)
t3 = t2 - 2^(n - 1)
t3 = 23 - 2^(3 - 1)
t3 = 23 - 2^2
t3 = 23 - 4
t3 = 19
The recursive formula is
tn = t_(n -1) - 2^(n - 1) Answer Recursive.